Shoot Nutrient Content and Nutrient Resorption of Leymus chinensis in Various Legume Mixtures - Li, Qiang; Chen, Xiaoying; Zhou, Daowei (Frontiers in Plant Science, 2018)
The objective was to determine soil properties, and shoot nutrients and nutrient resorption of typical Eurasian steppe species Leymus chinensis in various legume mixtures (legume abundance was 0, 25, 50 and 75%). Mixtures with 25 or 50% legume significantly increased soil moisture and soil [N, P] availabilities. Increasing legume abundance enhanced stem and total biomass of green L. chinensis shoots, further enhanced the proportion of stem biomass by 14-24% in senesced L. chinensis shoots. Legume mixtures, especially 50% legume, enhanced green and senesced organs N concentrations and N pools of L. chinensis. Similarly, mixtures with 25 or 50% legume enhanced P concentration and pool of senesced L. chinensis shoots, whereas both were decreased by 75% legume. As legume abundance increased, contribution ratios of stem to total N and P pools of senesced chinensis shoots increased from 25 to 32 and 25 to 33%, respectively. Mixtures, especially 25 or 50% legume, decreased N and P resorption efficiency (NRE) of L. chinensis shoots, whereas 75% legume increased PRE of L. chinensis. Total resorbed nutrients may remain stable under varying soil conditions for L. chinensis, and resorption of nutrients was symmetric between leaf and stem. In conclusion, legume abundance affected nutrient uptake and return of grass in mixed grasslands, but high legume abundance meant no low N resorption and high litter N content of grass. Furthermore, with increasing legume abundance, stems had more important roles in driving plant production, nutrient utilization and nutrient return of L. chinensis.